A decoupled stabilized finite element method for the dual‐porosity‐Navier–Stokes fluid flow model arising in shale oil. Issue 3 (11th December 2020) - Gao, Liang; Li, Jian
Abstract: In this paper, we consider the decoupled stabilized finite element method for the dual‐porosity‐Navier–Stokes model coupling the free flow region and the microfracture‐matrix system by using four interface conditions on the interface. The stabilized finite element method is decoupled in two levels, and it allows the coupling problem to be divide into three subproblems in a non‐iterative manner, which improves the computational efficiency. In addition, the stability and convergence of the decoupling scheme are also analyzed. Finally, the theoretical results are illustrated by some numerical experiments.